Phospholamban interacts with HAX-1, a mitochondrial protein with anti-apoptotic function - Vafiadaki, E.; Sanoudou, D.; Arvanitis, DA; Catino, D. H.; Kranias, EG; Kontrogianni-Konstantopoulos, A. (J Mol BiolJ Mol BiolJ Mol Biol, 2007)
Phospholamban (PLN) is a key regulator of Ca(2+) homeostasis and contractility in the heart. Its regulatory effects are mediated through its interaction with the sarcoplasmic reticulum Ca(2+)-ATPase, (SERCA2a), resulting in alterations of its Ca(2+)-affinity. To identify additional proteins that may interact with PLN, we used the yeast-two-hybrid system to screen an adult human cardiac cDNA library. HS-1 associated protein X-1 (HAX-1) was identified as a PLN-binding partner. The minimal binding regions were mapped to amino acid residues 203-245 for HAX-1 and residues 16-22 for PLN. The interaction between the two proteins was confirmed using GST-HAX-1, bound to the glutathione-matrix, which specifically adsorbed native PLN from human or mouse cardiac homogenates, while in reciprocal binding studies, recombinant His-HAX-1 bound GST-PLN. Kinetic studies using surface plasmon resonance yielded a K(D) of approximately 1 muM as the binding affinity for the PLN/HAX-1 complex. Phosphorylation of PLN by cAMP-dependent protein kinase reduced binding to HAX-1, while increasing concentrations of Ca(2+) diminished the PLN/HAX-1 interaction in a dose-dependent manner. HAX-1 concentrated to mitochondria, but upon transient co-transfection of HEK 293 cells with PLN, HAX-1 redistributed and co-localized with PLN at the endoplasmic reticulum. Analysis of the anti-apoptotic function of HAX-1 revealed that the presence of PLN enhanced the HAX-1 protective effects from hypoxia/reoxygenation-induced cell death. These findings suggest a possible link between the Ca(2+) handling by the sarcoplasmic reticulum and cell survival mediated by the PLN/HAX-1 interaction.
Keywords: Adaptor Proteins, Signal Transducing; Adult; Animals; Apoptosis/*drug effects; Calcium-Binding Proteins/*pharmacology; Humans; Mitochondrial Proteins/*metabolism/physiology; Myocardium/metabolism/*pathology; Phosphorylation; Proteins/*metabolism